An Innovative Technique of Microsurgical Training on Fresh “Chicken Quarter” Model: Our Experience - Boro, Sumanjit S.; Mathew, Anil K.; Kumar, Anchit (Indian Journal of Plastic Surgery, 2023)
Purpose Regular practice, quality clinical exposure, and academic discussion are essential in any surgical specialty training. This study discusses and validates the option of using a fresh “chicken quarter” model with a measurable scoring system, as a standard training regimen in microvascular surgery. This can be a very effective, economical, and easily accessible model for residents.Materials and Methods This study was conducted in the Department of Plastic surgery, from October 2020 to May 2021. Twenty-four fresh “chicken quarter” specimens were dissected and the ischial arteries and femoral veins' external diameter (ED) were measured. The microsurgical skills of the trainee were assessed in 6 months intervals using the Objective Structured Assessment of Technical Skills Scale (OSATS) as well as the time taken for anastomosis. All the data were analyzed using SPSS (statistical package for social sciences) version 21.Results A task-specific score value of 50% on October 2020 improved to 85.7% by May 2021. This was found to be statistically significant (p = 0.043). The mean ED of the ischial artery and femoral vein was 2.07 and 2.26 mm, respectively. The mean width of the vein measured at the lower one-third of the tibia was 2.08 mm. A greater than 50% reduction in anastomosis time was observed after a period of 6 months.Conclusion In our minimal experience, the “chicken quarter model” with OSATS scoring system seems to be effective, economical, very affordable, and easily accessible microsurgery training model for the residents. Our study is done only as a pilot project due to limited resources and we have the plan to introduce it as a proper training method in the near future with more residents.
Keywords: microvascular surgery; anastomosis; chicken quarter model; OSATS; COVID-19